Key Factors to Promote Industry 4.0 Readiness at Indonesian Textile and Clothing Firm - Ferly Norman (Bina Nusantara University, 2020)
This study discusses whether challenges, barriers, and key factors are the readiness of Indonesian Textile and Clothing (TC) firm in adopting Industry 4.0 (I4.0). The research method is by distributing questionnaires with closed questions to TC employees and owners firm. Respondents were given 15 barriers factors of adoption of I4.0 and gave weight with Likert scale method based on the situation in their company. The survey results were then tested by 2 experts from TC company executives and senior researchers from research institutes. The results of the study show that there are 5 major Barrier Factors with an average value of ≥ 4.0 (